2018
DOI: 10.1111/dmcn.13919
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal baclofen in metachromatic leukodystrophy

Abstract: Metachromatic leukodystrophy (MLD) is a rare progressive neurological disorder, often accompanied by motor impairments that are challenging to treat. In this case series, we report the course of treatment with intrathecal baclofen (ITB), aimed at improving daily care and comfort in children and young adults with MLD. All patients with MLD in our centre on ITB treatment for a minimum of 6 months were included (n=10; 4 males, 6 females; mean age 10y 8mo [range 6–24y]). Eight patients had MLD with a predominant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…Still, no effective treatment has been found for symptomatic MLD patients [3, 79]. For these patients, symptomatic treatments as botulinum toxin or intrathecal administration of baclofen can be helpful to treat spasticity [80]. The following paragraphs provide a summary of the results of preclinical studies and clinical trials targeting HCT, gene therapy, enzyme replacement therapy (ERT), and warfarin administration, with emphasis on the treatment effects on the PNS.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Still, no effective treatment has been found for symptomatic MLD patients [3, 79]. For these patients, symptomatic treatments as botulinum toxin or intrathecal administration of baclofen can be helpful to treat spasticity [80]. The following paragraphs provide a summary of the results of preclinical studies and clinical trials targeting HCT, gene therapy, enzyme replacement therapy (ERT), and warfarin administration, with emphasis on the treatment effects on the PNS.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Intrathecal baclofen has been widely used for spasticity management in children, mostly with cerebral palsy and brain injury, although some recent studies have shown promising effects of baclofen pumps on tone in patients with lysosomal storage deficiencies such as metachromatic leukodystrophy, 9,10 mucopolysaccharidosis type II, 11 or Gaucher disease. 12 It allows for the treatment of spasticity with fewer side effects such as liver toxicity, sedation, or secretion management.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] A handful of publications have discussed the effect of baclofen pumps in patients with neurodegenerative metabolic disease. [9][10][11][12] There has been no literature about using intrathecal baclofen in cases of Niemann-Pick. An informal survey on the Pediatric Intrathecal Baclofen Pump Network of 200 baclofen pump providers across North America and Europe also yielded no known cases of using intrathecal baclofen for Niemann-Pick.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, many of these drug-refractory patients experience significant symptomatic improvement after baclofen intrathecal infusion pump or deep brain stimulation (DBS) following an appropriate selection process. Intrathecal baclofen pump has been indicated in several patients with spasticity or severe dystonia and progressive IEMs, in some cases for palliative purposes, for example: Niemann Pick disease type C (153), Sjögren-Larsson syndrome (154), Metachromatic leukodystrophy (155), and Gaucher disease type 2 (156). Regarding DBS, Supplementary Table 4 describes the role and evidence of DBS in selected IEMs and childhoodonset MD.…”
Section: Step 5 Treatment Of Pediatric Metabolic Movement Disordersmentioning
confidence: 99%